MENINGKATKAN KECEPATAN TENDANGAN SABIT DENGAN MENGGUNAKAN KARET BAN PADA ATLET PENCAKSILAT DI CLUB SMA NEGERI 1 BARUSJAHE TAHUN AJARAN 2022/2023. - PURBA, JOEN PARNINGOTAN; SILALAHI, EKA KARTIKA; PURBA, FRIKSON JONY; MANALU, RIZKI BASTANTA B.; NAINGGOLAN, ASER PAUL (LP2MTBM MAKARIOZ, 2023)
This research aims to increase the speed of the sickle kick in pencak silat athletes at the SMA Negeri 1 Barusjahe Club for the 2022/2023 Academic Year by using rubber tires. Problem identification included a lack of speed of the scythe, stiffness and inefficiency of the kick, as well as the ease with which the kick was caught by the opponent. This study was limited to increasing the speed of the sickle kick through the use of tire rubber. The formulation of the problem raised includes the implementation, results, and effects of the use of tire rubber in increasing the speed of the sickle kick. The purpose of the study is to determine the implementation, results, and increase of the speed of the sickle kick using rubber tires. The benefits of this research are expected to help pencak silat athletes improve their sickle kick performance and provide a reference for future research in the same field.